Two new gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) from Trachinus spp. (Osteichthyes: Trachinidae) in the Gulf of Hammamet, Tunisia - Ghanmi, Nessrine; González-Solís, David; Gargouri, Lamia (Systematic parasitology, 2018)
Based on light and scanning electron microscopical studies, two new gonad-infecting species of Philometra Costa, 1845, P. draco n. sp. and P. radiata n. sp. (Nematoda: Philometridae), are described from the marine perciform fishes Trachinus draco (Linnaeus) and T. radiatus (Linnaeus) (both Trachinidae), respectively, in the Gulf of Hammamet, off the northeastern coast of Tunisia. Philometra draco n. sp. and P. radiata n. sp. can be separated from other gonad-infecting species of this genus by the structures associated to the gubernaculum (e.g. dorsal protuberance, smooth field separating the dorsolateral longitudinal parts), as well as by the length of the body, spicules and gubernaculum. Philometra radiata n. sp. can be distinguished from P. draco n. sp. in having the dorsal side of the gubernaculum distal end provided with a median longitudinal smooth field demarcated by two dorsolateral lamellate parts. These two new species are the first philometrid species described from fishes of the family Trachinidae.
Keywords: Gonads; Dracunculoidea; Tunisko; Tunisia; gonády; zvířata; mikroskopie elektronová rastrovací; Perciformes; Microscopy, Electron, Scanning; Animals; Species Specificity; druhová specificita